EMOTIONALIZATION OF CRIMINAL LAW IN THE PROCESS OF ADOPTING AND AMENDING CRIMINAL LEGISLATION - Marković, Ivana; Zdravković, Miloš (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The authors deal with the phenomenon of emotionalization of criminal law, which emanates itself in three stages – in the legislative process, within the content of the respective provisions and in the criminal procedure. While the third stage is well-identified as such and procedural principles aim to guarantee impartiality; and discussions on negative feelings accompanied the dogmatical upgrading of hate as an obligatory aggravating circumstance, the process of adopting and amending criminal legislation in an emotionalized context remained mostly in the background. Afte showing the relevance and topicality of the issue, the authors connect it with the basic goal of law and legitimacy of state power, give various definitions and explain the notion of emotions, show its prior existеnce on a historical example, continuing with a contemporary-comparative one and, finally, analysing the recent Amendments to the Criminal Code of Serbia in this context.